Kecemasan Orang Tua Yang Memiliki Anak Dengan Penyakit Kanker Selama Pandemi Covid-19 - Salsabila Putri Aulia; Hellena Deli; Wan Nishfa Dewi (Poltekkes Kemenkes Semarang, 2021)
Backgrounds: during the Covid-19 pandemic, many parents who had children with cancer experienced anxiety due to changes in their child's care. And if the anxiety is not addressed, parents become unresponsive to their children's needs thus further negatively affect their children's conditionPurpose: this study aims to describe the anxiety of parents who have children with cancer during the Covid-19 pandemic.Methods: this study use descriptive research design and non-probability sampling (consecutive sampling technique) to select 30 respondents. This study also used Corona Pandemic Anxiety Scale-11 item (CPAS-11) questionnaire to collect data and was analyzed using uni-variate analysisResults: the results of the analysis 0f 30 respondents, the majority are in early adulthood (60%), are mothers (76.7%), last education high school (50%), have a child with stage 2 cancer (53.3%), and the length of time the child has suffered is 0-5 years (96.7%). Researchers then found the majority of parents in this study (50%) experienced moderate levels of anxiety, and the majority of parents with severe anxiety levels had children at school age (6-12 years) (25%), had children with 0-5 years of suffering. (17.2%), and having a child with stage 2 cancer (18.8%).Conclusion: most of the parents involved in this study experienced moderate levels of anxiety with various accompanying characteristics. The result of this research can be used as a literature study for nursing students to collaborate with the hospital in developing and finding appropriate interventions to overcome anxiety in parents with children with cancer.